Компьютерное моделирование аварийных режимов в электрических сетях и электрооборудовании - Shmakov, Михаил; Ivanovich, Александр; Chaychits, Николай (Vestnik of the Institute for Command Engineers of the MES of the Republic of Belarus, 2010)
The possibility of application of computer modeling with the use of virtual electronic laboratory EWB Multisim 9 has been considered for various modes in networks and electric equipment including the case of emergencies. By a number of examples, the effectiveness of such approach, for instance, for practical training purpose has been shown. It has been pointed out the possibility of working out effective verification tools and prevention of consequences of emergencies modes.